Malignant Pleural Effusion, an Unusual Presentation of Metastatic Adenoid Cystic Carcinoma: A Case Report and Review of the Literature - Arshad, MD, Ayesha (North American Journal of Medicine and Science, 2017)
Adenoid cystic carcinoma (ACC) is an uncommon malignant neoplasm of the major and minor salivary glands that is known to have a long clinical course, behaving in an insidious and indolent fashion with multiple recurrences preceding distant metastasis. Reported here is a case of a patient presenting with shortness of breath and recurrent pleural effusion. Exfoliated ACC cells were observed on cytological evaluation, a rare occurrence. Mediastinal lymph node involvement was also confirmed on cytology. A primary site of origin was not found. In summary ACC can present in various body sites and pathologists should consider ACC in the differential diagnosis of a basaloid carcinoma of uncertain origin. [N A J Med Sci. 2017;10(1):8-12. DOI: 10.7156/najms.2017.1001008]